Analysis of Factors Affecting Employment Absorption in Micro and Small-Scale Industries Across 34 Provinces in Indonesia - Muhammad Iqbal Mohar Harahap; Fitrawaty Fitrawaty; Muhammad Fitri Rahmadana (Universitas Negeri Semarang, 2026)
The micro and small-scale industry (MSI) sector constitutes a key driver of employment in Indonesia; however, its labor absorption capacity varies across regions. This study examines the determinants of employment absorption in MSI across 34 provinces using panel data regression. The model includes production value, investment, wages, and the number of business units as explanatory variables. The results indicate that investment and the number of business units have a positive and statistically significant effect on employment absorption, while wages show a negative and significant relationship. In contrast, production value is not statistically significant. These findings suggest that output expansion in the MSI sector is not consistently associated with increased labor absorption. However, this condition should be interpreted cautiously and does not necessarily imply structural jobless growth. From a theoretical perspective, the findings reveal a partial inconsistency with conventional labor demand theory, particularly regarding the expected positive relationship between output and labor demand. This may reflect structural characteristics of MSI, such as low productivity and heterogeneous production conditions. Policy implications should remain aligned with the empirical results, emphasizing investment promotion and business expansion to improve employment absorption.